Diadelophora, a new phorid genus from central and western Brazil (Diptera: Phoridae) - Ament, Danilo César (Zootaxa, 2024)
Diadelophora gen. nov, a conspicuous new genus of phorid flies is described based on two species from central and western Brazil, D. stilbella sp. nov. and D. inornata sp. nov. The new genus is positioned in the Thaumatoxena-group within the subfamily Phorinae, probably as sister group to Hypocerides Schmitz, 1915. The diagnostic features of Diadelophora are commented and illustrated, and the genus differences to Hypocerides are highlighted. The morphology of Diadelophora species is explored in detail with SEM, photos, and optical microscopy illustrations of structures of taxonomic relevance and other curious features of the genus.